BS EN 4012. Aerospace series. Nuts, bihexagonal, self-locking, in heat resisting nickel base alloy NI-PH2601 (Inconel 718), MoS2 coated. Classification: 1 550 MPa (at ambient temperature) / 425 °C. (29th June 2023) - British Standards Institution,
No abstract available